2018
DOI: 10.3390/ijms19092785
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism and Health Role of Functional Ingredients in Blueberry for Chronic Disease in Human Beings

Abstract: Functional ingredients in blueberry have the best health benefits. To obtain a better understanding of the health role of blueberry in chronic disease, we conducted systematic preventive strategies for functional ingredients in blueberry, based on comprehensive databases, especially PubMed, ISI Web of Science, and CNKI for the period 2008–2018. Blueberry is rich in flavonoids (mainly anthocyanidins), polyphenols (procyanidin), phenolic acids, pyruvic acid, chlorogenic acid, and others, which have anticancer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 134 publications
1
82
0
Order By: Relevance
“…For the in vitro test we have obtained promising results which can be compared with available published data. Many studies have proved that anthocyanins present beneficial effects for human health [ 47 ]. Because of their physiological activities, the consumption of anthocyanins may play a significant role in preventing lifestyle-related diseases such as cancer, diabetes, cardiovascular and neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…For the in vitro test we have obtained promising results which can be compared with available published data. Many studies have proved that anthocyanins present beneficial effects for human health [ 47 ]. Because of their physiological activities, the consumption of anthocyanins may play a significant role in preventing lifestyle-related diseases such as cancer, diabetes, cardiovascular and neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been shown that blueberries play an important role in hepatic protection and hepatic fibrosis reversal. 8 Moreover, an increasing number of studies have revealed that probiotics act as a complementary therapeutic method in NAFLD. 9 However, little is known about the impacts of blueberry juice combined with probiotics (BP) on NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanin belongs to flavonoids, and flavonoids belongs to polyphenols. Black, purple, and blue barley grains have gained much attention recently because their anthocyanins have anticancer, glycemic and body weight regulation, antioxidation, anti-inflammation, neuroprotection, hypolipidemia, retinal protection, hepatoprotection, and antiaging effects [150,151].…”
Section: Polyphenols Mechanismmentioning
confidence: 99%
“…The worldwide daily consumption of fruits and vegetables as well as tea has become the main tool for prevention of cardiovascular disease, stroke, cancer and diabetes due to their polyphenols modulate tau hyperphosphorylation and beta amyloid aggregation [178]. The anthocyanins and polyphenols for major functional ingredients in blueberry played a key role in preventing 15 chronic diseases [151]. The organopolysulfides and quercetin for major functional ingredients in Allium genus played a key role in preventing 10 chronic diseases [179].…”
mentioning
confidence: 99%